2013
DOI: 10.1016/j.joca.2013.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitors increase microRNA-146a expression and enhance negative regulation of interleukin-1β signaling in osteoarthritis fibroblast-like synoviocytes

Abstract: Our study demonstrated that HDAC inhibitor treatment in OA-FLS significantly increased miR-146a expression and mediated markedly negative regulation to inhibit IL-1β-induced signaling and cytokine secretion. Our results indicate the potential rationale of anti-inflammatory effects for HDAC inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 37 publications
3
70
0
Order By: Relevance
“…This result suggested a negative feedback between miR146a and inflammatory factors, considering that miR-146a was up-regulated in the RA pathology, and the administration of miR-146a may serve as a novel therapeutic target for bone destruction in RA [45]. The negative feedback of miR-146a with inflammatory factors was further confirmed in osteoarthritis fibroblast-like synoviocytes [46], osteoarthritis pain in knee joints [47], and intervertebral disc [48]. Apparently, there is still a great controversy on the role of miR-146a with two opposite conclusions, and one study reported a downregulation of miR-146 in OA cartilage, further mystifying the issue [49].…”
Section: Discussionmentioning
confidence: 65%
“…This result suggested a negative feedback between miR146a and inflammatory factors, considering that miR-146a was up-regulated in the RA pathology, and the administration of miR-146a may serve as a novel therapeutic target for bone destruction in RA [45]. The negative feedback of miR-146a with inflammatory factors was further confirmed in osteoarthritis fibroblast-like synoviocytes [46], osteoarthritis pain in knee joints [47], and intervertebral disc [48]. Apparently, there is still a great controversy on the role of miR-146a with two opposite conclusions, and one study reported a downregulation of miR-146 in OA cartilage, further mystifying the issue [49].…”
Section: Discussionmentioning
confidence: 65%
“…This was accompanied by Smad4 downregulation, VEGF upregulation, and increased chondrocyte apoptosis. miR-146a expression is also induced by HDAC inhibitor treatment in synovial fibroblasts isolated from OA patients [58]. This study showed that HDAC inhibitor treatment increased NF-κB binding to the promoter region of the miR-146a gene.…”
Section: Role Of Microrna In Articular Cartilage Homeostasis and Ostementioning
confidence: 92%
“…Previously, it was shown that HDACi treatment could rapidly alter miR expression levels, either increasing or decreasing certain subsets of micro-RNA. [50][51][52][53] Future studies should include dissecting how and why HDACi differentially regulate the expression of miR subsets. Investigating whether different classes of HDACi affect miR expression similarly may lead to a better understanding of HDACi treatments and the epigenetic regulation of miRs.…”
Section: Discussionmentioning
confidence: 99%